Synthesis of ZnO-Fe3O4 Magnetic Nanocomposites through Sonochemical Methods for Methylene Blue Degradation - Nanda Saridewi; Sri Komala; Agustino Zulys; Siti Nurbayti; Latifah Tulhusna; Adawiah Adawiah (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Textile industry waste can pollute the aquatic environment because it contains dye contaminants with very stable properties that are difficult to degrade naturally. However, dye contaminants degradation can be carried out by photodegradation using ZnO-Fe3O4 magnetic nanocomposite photocatalysts. This study aims to synthesize ZnO-Fe3O4 magnetic nanocomposite through a sonochemical method. Then measure their photocatalytic activity in methylene blue degradation. The best ZnO-Fe3O4 magnetic nanocomposite is made of ZnO:Fe3O4 mass ratio of 4:1 with a crystal size of 31.058 nm, a hexagonal crystal phase and a particle size of 173.23 nm. The ZnO-Fe3O4 magnetic nanocomposites (4:1) provides optimum degradation capacity of methylene blue under halogen lamp irradiation of 99.56 mg/g at pH 13. Furthermore, the ZnO-Fe3O4 magnetic nanocomposites had good stability in 10 cycles reaction with a degradation capacity of 99.24-99.75 mg/g. The photocatalytic degradation of methylene blue by ZnO-Fe3O4 occurs through the formation of free radical species with hydroxyl radicals as the dominant species that play an important role in the degradation process. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).